Come back, Amelia Bedelia - Parish, Peggy; Tripp, Wallace (New York : Harper & Row, 1971)
Because she does exactly as she is told, Amelia Bedelia is fired from one job after another
160
Accelerated Reader AR
Keywords: Work -- Juvneile fiction; Humorous stories